Molecular biomechanics of seed germination in Arabidopsis thaliana and Lepidium sativum - Ghita, Melania Georgeta (2014)
Seed germination is a key process in world agriculture. For this reason, the capacity of a seed to germinate with minimum input from farmers is highly desirable, keeping the production costs as low as possible. The physiological mechanism of germination is well known, involving the rupture of the endosperm and testa envelope by the expanding embryo, but the molecular and biomechanical changes underlying this process are poorly understood. In order to answer the question of how the plant developmentally regulates changes in cell wall stiffness associated with germination, an innovative molecular biomechanics approach was developed. It combines biophysical, engineering and molecular biology approaches. A comparative approach was taken using the related species Arabidopsis thaliana and Lepidium sativum, the former due to the wealth of genomic resources, and the latter due to larger size and ease of use in biomechanics experiments. Environmental scanning electron microscopy imaging revealed that the endosperm structure is intact after protrusion of the radicle, confirming the fact that rupture occurs between individual cells. Germination is a process that requires targeted cell separation or/ and cell wall remodeling. For this reason, following the predictions of the gene network SeedNet, containing the endosperm-specific sub-network cluster 19 (Bassel et al., 2011), endosperm specific genes were studied. In order to localize their expression, promoter::GUS constructs were used for the genes DELTA-VPE, SCPL51 and DOF2.1, and different mutant alleles of four transcription factors from cluster 19 (athb23, bhlh-115, bee2 and dof2.1) were screened to identify changes in germination behaviour. DELTA-VPE and SCPL51 were proven to be endosperm specific and ABA insensitive. DELTA-VPE was GA insensitive and SCPL51 expression required GA. Also, DELTA-VPE expression could be observed after 15 minutes of imbibition in the whole endosperm, while SCPL51 showed a temporal expression requiring 18 hours of imbibition before being observed in all endosperm cells. The analysed T-DNA lines showed an epistatic relationship between ATHB23 and DOF 2.1 and a decreased sensitivity to stress factors like osmotic and salt stresses, than the wild type. Using nanoindentation, a differentiation between different regions of endosperm was attempted, but the methodology was not sensitive enough. However, different elastic modulus values for imbibed and dry Lepidium seeds were registered. To image the internal changes in seed structure during germination, micro-CT was used, estimating values for endosperm thickness from dry state to germinated one. This work enforces the knowledge of the molecular biology and biomechanical properties of the endosperm.